Kecerdasan Emosional Terhadap Kepemimpinan Mahasiswa Di Universitas Negeri Makassar - Ramlah Ramlah; Annisa Putri Maharani; Berliana Devayanti (Contemporary Education Review, 2025)
This research aims to investigate the role of emotional intelligence in leadership development among students. Emotional intelligence is understood as the ability to recognize, understand and regulate the emotions of both oneself and others. In this study, analysis was carried out on the relationship between emotional intelligence and leadership effectiveness through data collection carried out in several organizational environments at Makassar State University. This research reveals that students who have high emotional intelligence tend to be better at motivating themselves and others, as well as at establishing positive relationships within teams. The research results are expected to provide insight for educational institutions in designing more effective leadership training programs and identifying the ideal profile of student leaders with a high level of emotional intelligence. Thus, this research is not only relevant to the acad